Perdagangan dan Eksploitasi Kayu Eboni di Sulawesi Tengah pada Masa Kolonial: Sebuah Tinjauan Awal - Setiawan, Adi (Lembaran Sejarah, 2023)
Diospyros celebica Bakh, commonly known as ebony or black ebony,is one of the endemic species found on the island of Sulawesi, Indonesia. This exquisite wood has been in high demand globally due to its aesthetic appearance, resulting in its trade for many years since the pre-colonial period. This paper aims to explore the history of ebony in the global trade network and its exploitation in Central Sulawesi in the first half of the 20th century. This paper relied on a variety of sources including newspapers, government documents, botanical magazines, and other literature related to the topic. This paper reveals that the exploitation of ebony during the colonial period was massive, especially during the 1930s. Europe, America, and Japan were the primary export destinations for ebony, with Japan being the largest consumer of this wood. The significant exploitation of ebony raised concerns for the Dutch East Indies as it became increasingly scarce by the end of the 1930s.